2015
DOI: 10.1097/dad.0b013e3182974558
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Complications Related to Tattooing

Abstract: : Although tattooing is an ancient practice, its increasing popularity and social acceptance, variability of tattoo ink composition, sporadic reports of novel tattoo reactions and advances in the field of tattoo removal techniques make it a topic of immense interest among dermatologists and pathologists alike. Since effective legislation governing the tattoo industry is largely lacking in most regions of the world, it is important to recognize the range of tattoo-related complications from a dermatopathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 107 publications
1
8
2
Order By: Relevance
“…In a critical review, Thum et al showed that inflammatory complications related to tattooing are associated with a wide spectrum of histological reaction patterns. Consistent with what they described, and probably because of the variety of chemical substances present in modern tattoo inks, we could not directly associate a type of histopathological reaction to a specific color (Thum & Biswas, 2015).…”
Section: Relationship Between Cutaneous Reactions Ink Color and Histo...supporting
confidence: 84%
“…In a critical review, Thum et al showed that inflammatory complications related to tattooing are associated with a wide spectrum of histological reaction patterns. Consistent with what they described, and probably because of the variety of chemical substances present in modern tattoo inks, we could not directly associate a type of histopathological reaction to a specific color (Thum & Biswas, 2015).…”
Section: Relationship Between Cutaneous Reactions Ink Color and Histo...supporting
confidence: 84%
“…Tattooing is a common practice performed for cosmetic appearance and cultural beliefs. Adverse reactions to tattooing can occur with different morphologies and histopathologic reaction patterns [11]. Delayed cutaneous reactions can also occur, usually due to red pigment, and include granulomatous, allergic, lichenoid, and pseudolymphomatous reactions [2].…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Most frequently observed patterns were mixed and included fibrosis, interface activity and major signs of type IV reactions like spongiosis and acanthosis. 38,[40][41][42] Severe allergic reactions do usually not respond to medical treatment with corticosteroids and often need complete removal of the colorant from the skin, which can be achieved by surgical or CO 2 -laser removal. 43,44 In a small German case series, even superficial removal of affected tattoos was sufficient to provide cure and aesthetically acceptable results in three patients.…”
Section: Inflammatory Tattoo Reactions and Prevalencementioning
confidence: 99%
“…Histologically, tattoo complications are characterized by severe inflammation with a high share of lymphocytes, histiocytes and macrophages 38–40 . Most frequently observed patterns were mixed and included fibrosis, interface activity and major signs of type IV reactions like spongiosis and acanthosis 38,40–42 . Severe allergic reactions do usually not respond to medical treatment with corticosteroids and often need complete removal of the colorant from the skin, which can be achieved by surgical or CO 2 ‐laser removal 43,44 .…”
Section: Introductionmentioning
confidence: 99%